Cognitive-Behavioral Therapy for Anxiety in Parkinson's Disease. Issue 4 (July 2020) - Reynolds, Gretchen O.; Saint-Hilaire, Marie; Thomas, Cathi A.; Barlow, David H.; Cronin-Golomb, Alice
Parkinson's disease (PD) is characterized by motor symptoms, but nonmotor symptoms also significantly impair daily functioning and reduce quality of life. Anxiety is prevalent and debilitating in PD, but remains understudied and undertreated. Much affective research in PD focuses on depression rather than anxiety, and as such, there are no evidence-based treatments for anxiety in this population. Cognitive-behavioral therapy (CBT) has shown promise for treating depression in PD and may be efficacious for anxiety. This exploratory study implemented a multiple-baseline single-case experimental design to evaluate the utility and feasibility of CBT for individuals with PD who also met criteria for a DSM-5 anxiety disorder ( n = 9). Participants were randomized to a 2-, 4-, or 6-week baseline phase, followed by 12 CBT sessions, and two post treatment assessments (immediately post treatment and 6-week follow-up). Multiple outcome measures of anxiety and depression were administered weekly during baseline and intervention. Weekly CBT sessions were conducted in-person ( n = 5) or via secure videoconferencing ( n = 4). At post treatment, seven of the nine participants showed significant reductions in anxiety and/or depression, with changes functionally related to treatment and most improvements maintained at 6-week follow-up. Effects of CBT on secondary outcomes varied across participants, with preliminary evidence for reduction in fear of falling. Adherence and retention were high, as were treatment satisfaction and acceptability. The findings of this pilot study provide preliminary evidence for the utility of CBT as a feasible treatment for anxiety and comorbid depressive symptoms in PD and highlight the potential of telehealth interventions for mood in this population.